Pirfenidone Alleviates Choroidal Neovascular Fibrosis through TGF-β/Smad Signaling Pathway - Chuang Gao; Xin Cao; Lili Huang; Yueqi Bao; Tao Li; Yue Di; Liucheng Wu; Yu Song (Journal of Ophthalmology, 2021)
Background. Transforming growth factor-β (TGF-β) plays a major role in CNV. However, the mechanism is unclear. This study investigates the effect of Pirfenidone (PFD) on TGF-β/Smad signaling pathway on the development of choroidal neovascular fibrosis in choroidal neovascularization (CNV) mouse model. C57BL/6J male mice (aged from 6 to 8 weeks) received intravitreal injections of phosphate-buffered saline (PBS)/PFD solution on 14 days after laser injury. Mice were anesthetized by intraperitoneal injection of 4% pentobarbital (0.05 mg/g body weight). Optical Coherence Tomography (OCT), Fundus Fluorescein angiography (FFA), and hematoxylin-eosin (HE) were used to assess CNV formation. The fibrosis area was monitored by staining the collagen type I (Col-I). Western blotting was used to analyze the expression of TGF-β2, Smad 2/3, phosphorylated Smad 2/3 (p-Smad 2/3), and α-smooth muscle actin (α-SMA). Terminal deoxynucleotidy1 transferase dUTP nick-end labelling (TUNEL) assay was performed on cryosections of mouse eyes to detect apoptosis. Our data showed PFD inhibited areas of fibrosis during day 21 to day 28. We also found that the levels of TGF-β2 protein expressions increasingly reached the peak till the 3rd week during the CNV development. The protein levels of Smad 2/3, p-Smad 2/3, and α-SMA also increased significantly in CNV mice, but this response was profoundly suppressed by the TGF-β inhibitor PFD. The results of this study suggest that TGF-β2 represents a target to prevent or treat choroidal neovascular fibrosis, and PFD may provide an alternative to traditional methods for Wet Age-related macular degeneration (wAMD) treatment.